2020
DOI: 10.1016/j.surg.2020.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of malignancy for patients older than 40 years with appendicitis and an appendix wider than 10 mm on computed tomography scan: A post hoc analysis of an EAST multicenter study

Abstract: Background: The incidence of underlying malignancy in appendicitis ranges between 0.5% and 1.7%. We sought to identify the subset of patients with appendicitis who are at increased risk of appendiceal malignancy. Methods: Using the Eastern Association for the Surgery of Trauma Multicenter Study of the Treatment of Appendicitis in America: Acute, Perforated, and Gangrenous database, we included all patients from 28 centers undergoing immediate, delayed, or interval appendectomy between 2017 and 2018. Univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
5
13
0
1
Order By: Relevance
“…Potential missed appendiceal malignancy is a clinical concern of non-operative management. This study found four cases of malignancy and three neuroendocrine tumours in the initial non-operative management group, and an overall rate of malignancy of 1.3 per cent, consistent with the population reported incidence of 0.5-1.7 per cent 26 . Known risk factors for appendiceal malignancy are age, appendiceal dilatation on CT and complicated appendicitis 26,27 .…”
Section: Discussionsupporting
confidence: 88%
“…Potential missed appendiceal malignancy is a clinical concern of non-operative management. This study found four cases of malignancy and three neuroendocrine tumours in the initial non-operative management group, and an overall rate of malignancy of 1.3 per cent, consistent with the population reported incidence of 0.5-1.7 per cent 26 . Known risk factors for appendiceal malignancy are age, appendiceal dilatation on CT and complicated appendicitis 26,27 .…”
Section: Discussionsupporting
confidence: 88%
“…Our findings corroborate recent findings in prospectively collected data, analyzed post-hoc, from the MUSTANG trial (13). Taken together we concur that age older than 40 must be considered a risk factor for malignancy when considering appendectomy at initial presentation or at a later date (13,32).…”
Section: Discussionsupporting
confidence: 71%
“… 20 Increasing age increases the odds of a cancer diagnosis after appendectomy 35 and age >40 is associated with a greater risk of malignancy. 36 In the present study the proportion of CA increased with increasing age. Thus, the pros and cons of IA cannot be discussed without considering these two concerns.…”
Section: Discussionsupporting
confidence: 58%